Enemies of War - Cassidy, Esther (United States, 1992)
Soros Documentary Fund For nearly a decade, El Salvador had been experiencing the cruel intensity of civil war, a conflict reportedly fueled by billions of dollars in aid from the United States government. Then, in 1989, an unspeakable crime occurred, one that would shock the international community and eventually lead a nation towards peace. “Enemies of War” examines the horrific murders of six Jesuit priests and the subsequent political and social ramifications as seen through the eyes of a Salvadoran family, a United States congressman, an ex-ambassador and an American priest.